Efeito de estímulos emocionais e do humor na memória operacional visual - Siquara, Gustavo Marcelino (2019)
Recent studies seek to understand how emotional stimuli and emotional states can interfere with cognitive processes. Working Memory (WM) is an important cognitive function, for example, for learning and decision making. WM is the ability to manipulate information in the mind for a period of time. The aim of the present thesis was to evaluate the effect of images with emotional valence and humor alterations in the formation of object-oriented visual binding of WM. The thesis is divided into 2 empirical studies. In the empirical study I, the objective was to analyze the maximum recall capacity and the order of presentation of the emotional images in the formation of the object-location visual binding of WM. The specific objectives were to test the models of 'Slot' and Shared Capabilities of maximum binding capacity in different conditions and to evaluate the effect of the order of presentation of negative images in the recall of the images in the formation of object-location binding. 106 university students with no history of psychiatric or neurological disorders participated in this study. Images of the International Affective Picture System (IAPS) were used for the construction of the experiment. We selected 24 images, 12 of which were neutral emotional valence and 12 of negative emotional valence. The experiment was computerized and inserted inside the Unit platform in the C # language. Four experiments were carried out with different quantities and orders of presentation of the emotional images in a block series. In experiment 1, 4 images were presented per block, experiment 2, 6 images per block, experiment 3, 8 images per block, experiment 4, 12 images per block. The order of presentation of the neutral and negative images was different to test the hypotheses. For the data analysis, descriptive and inferential statistics were used with the Friedman, Wilcoxon, Kruskal-walls and post hoc tests of Connover and Dunn. The results of the experiments indicate that negative images capture more attentional resources while producing more "noise" in the formation of visual binding. That is why the amount of negative images and the order they are presented interferes with the formation of binding. Another finding is that you increase the amount of images presented the top-down control for prioritizing the bottom-up images. In the empirical study II the objective was to evaluate the relationship between Major Depression and its effect on the formation of visual object-location binding with emotional images. Additionally, the study aims to investigate the effect of humor induction on the visual object-location binding of emotional images with different interval times for recall. We selected 24 images, 12 of which were neutral emotional valence and 12 of negative emotional valence. The experiment was computerized and inserted inside the Unit platform in the C # language. It was used the experiment with 4 images, being 2 neutral and 2 negative in blocks of 4 images in a serial way. The participants were a total of 168 people who were divided into groups being 136 college students; 16 people with up to 2nd Full Degree; 16 with Psychiatric Diagnosis of Major Depression. Within the group of university students were divided into 4 groups. The first group with interval time for recall of 8 seconds and neutral mood, second group with interval time of 1 second and neutral mood, third group, interval time of 1 second and induced mood, and the fourth group, interval time of 8 seconds and induced mood. For the induction of negative mood was used the procedure of induction of humor of Velten. The results indicated that the induction of humor was not sufficient to significantly decrease the capacity of visual binding formation despite differences being found. The interval time for recall (1 second X 8 Seconds) was also not sufficient to significantly decrease binding capacity. When comparing the binding capacity between the University Groups, Non University and Major Depression, the University Group presented a better performance, followed by Non University students and the worse performance for the group with Major Depression. When analyzing the total of images recalled, dividing between the neutral and negative images between the three groups mentioned above, it was possible to observe that the negative images are more remembered than the neutral ones, nevertheless in the group with Major Depression this difference presented a larger size of It is made. The Major Depression group had a lower overall binding capacity, but a greater tendency to remember negative images. The study of the relationship between emotions and cognition remains a challenge to be won. The work with emotional images adds yet another important variable for the understanding of the phenomenon of codification and memory. Trying to find cognitive markers that help identify and risk Major Depression and human behavior continues to be a great stimulus for future research, although the present study has found promising results.